Four challenges when conducting bibliometric reviews and how to deal with them - Romanelli, João Paulo; Gonçalves, Maria Carolina Pereira; de Abreu Pestana, Luís Fernando [UNESP]; Soares, Jéssica Akemi Hitaka [UNESP]; Boschi, Raquel Stucchi; Andrade, Daniel Fernandes (Springer Nature, 2021)
The evidence base in environmental sciences is increasing steadily. Environmental researchers have been challenged to handle massive volumes of data to support more comprehensive studies, assess the current status of science, and move research towards future progress. Bibliometrics can provide important insights into the research directions by providing summarized information for several end users. Here, we present an in-depth discussion on the use of bibliometric indicators to evaluate research outputs through four case studies comprising disciplines in environmental sciences. We discuss four big challenges researchers may face when conducting bibliometric reviews and how to deal with them. We also address some primary questions researchers may answer with bibliometric mapping, drawing lessons from the case studies. Lastly, we clarify some misuses of review concepts and suggest methodological principles of systematic reviews and maps to improve the overall quality of bibliometric studies.
Keywords: Bibliometric indicators; Bibliometric mapping; Case studies; Environmental sciences; Network analysis; Research trends